Product Market Synergies and Competition in Mergers and Acquisitions: A Text-Based Analysis - Hoberg, Gerard; Phillips, Gordon (Review of Financial Studies, 2010)
We use text-based analysis of 10-K product descriptions to examine whether firms exploit product market synergies through asset complementarities in mergers and acquisitions. Transactions are more likely between firms that use similar product market language. Transaction stock returns, ex post cash flows, and growth in product descriptions all increase for transactions with similar product market language, especially in competitive product markets. These gains are larger when targets are less similar to acquirer rivals and when targets have unique products. Our findings are consistent with firms merging and buying assets to exploit synergies to create new products that increase product differentiation. The Author 2010. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oxfordjournals.org., Oxford University Press.